2018
DOI: 10.1002/hed.25420
|View full text |Cite
|
Sign up to set email alerts
|

Association between pretreatment obesity, sarcopenia, and survival in patients with head and neck cancer

Abstract: Background Body mass index (BMI), sarcopenia, and obesity‐related comorbidities have been associated with head and neck squamous cell carcinoma (HNSCC) progression. Methods We conducted a retrospective analysis of 441 normal‐weight, overweight, and obese HNSCC patients treated at Montefiore Medical Center (New York). Patients were grouped by BMI prior to treatment and assessed for differences in survival adjusting for comorbid conditions (cardiovascular disease and diabetes). Evidence of sarcopenia was also as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 31 publications
3
48
2
1
Order By: Relevance
“…In our study, the incidence rate of low SMM was 60.71%, which is higher than the incidence rates reported in other publications on low SMM in head and neck cancers, ranging from 6.6 to 64.6% (8,10,24,25). A possible explanation for this may be that the present study enrolled patients with locoregionally advanced cancers who were receiving CCRT, whereas more patients in early stages were included in prior studies.…”
Section: Discussioncontrasting
confidence: 65%
“…In our study, the incidence rate of low SMM was 60.71%, which is higher than the incidence rates reported in other publications on low SMM in head and neck cancers, ranging from 6.6 to 64.6% (8,10,24,25). A possible explanation for this may be that the present study enrolled patients with locoregionally advanced cancers who were receiving CCRT, whereas more patients in early stages were included in prior studies.…”
Section: Discussioncontrasting
confidence: 65%
“…The former had a much higher risk than any other research (HR = 3.93, 95% CI; 2.36-6.55). Interestingly, the cutoff value they used was the same as that from three other included articles (18,21,29) (Table 1), but the incidence rate of sarcopenia was only 6.6%; the possible reasons for this are as follows: (a) 6.6% is for sarcopenia with visceral obesity in their study, (b) the locally advanced cancer stage is the distinguishing property, or (c) there might be potential bias that affected the incidence. The study by Van Rijn-Dekker et al, which will soon be published in full, was a meeting abstract that investigated a large-scale cohort of 750 patients with HNSCC, the incidence of sarcopenia was also low, i.e., as 25%, and the result was conservative and narrow (HR = 1.44, 95% CI: 1.12-1.84).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Van Rijn-Dekker et al (26) found that sarcopenia is not a prognostic factor in early-stage HNSCC. Third, because Fattouh et al (29) only reported the positive HR in their multivariate analysis, the univariate meta-analysis included 10/11 of eligible primary studies; however, according to the principle of Cox regression, there is little chance that the conclusion of the meta-analysis will be affected. Finally, the reasons for the different statistical significance between Egger's test and the trim-and-fill method might derive from the low number of included studies; however, these studies are relatively new, and we did not receive replies from the authors of three conference articles with positive (49,50) and negative (51) results, which requires further evaluation after their official publication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients undergoing radiotherapy for HNC, recent studies have demonstrated independent associations between sarcopenia with reduced survival and chemotherapy dose‐limiting toxicities ( 16–26 ) , although no studies have examined myosteatosis. The present study aimed to examine the association between CT‐defined sarcopenia and myosteatosis on overall survival (OS), treatment completion, unplanned hospital admissions and associated costs for patients undergoing radiotherapy ± other treatment modalities (surgery and/or systemic therapy) for HNC.…”
Section: Introductionmentioning
confidence: 99%